Catheter ablation and thoracoscopic ablation in long persistent atrial fibrillation with large left atrium - Park, Chan Soon; Choi, Eue-Keun; Lee, So-Ryoung; Ahn, Hyo-Jeong; Kwon, Soonil; Kim, Sunhwa; Sohn, Suk Ho; Choi, Jae Woong; Hwang, Ho Young; Oh, Seil (Frontiers in Cardiovascular Medicine, 2022)
Background Pulmonary vein antrum isolation (PVAI) is the cornerstone of atrial fibrillation (AF) ablation, but the clinical outcomes of PVAI are unsatisfactory in patients with persistent AF and a large left atrium (LA). Objectives We investigated the clinical outcomes following radiofrequency ablation (RFCA), cryoballoon ablation (CBA), and thoracoscopic maze in patients with persistent AF and a large LA. Methods We included patients with consecutive persistent AF who had a large LA (LA diameter > 50 mm) and underwent RFCA, CBA, or thoracoscopic maze surgery. In the RFCA group, additional linear ablation was performed at the physician’s discretion. The endpoint was 12 months without recurrence of an atrial arrhythmia, including AF, atrial flutter, and atrial tachycardia, following a 90-day blanking period. Results We recruited 89 persistent AF patients with a large LA who underwent RFCA (n=32), CBA (n=38), or the thoracoscopic maze procedure (n=19). During the 12-month follow-up, 48 (53.9%) cases of AF recurrence were observed. There was no prognostic difference between groups (50.0% in RFCA vs. 52.6% in CBA vs. 63.2% in thoracoscopic maze, all P > 0.05). Early recurrence during the blanking period was a significant predictor of late recurrence for RFCA and CBA, but not for the thoracoscopic maze. Conclusion In persistent AF patients with a large LA, we did not find a prognostic difference RFCA, CBA, or a thoracoscopic maze procedure in recurrence of atrial arrhythmia. Early recurrence predicted late recurrence in catheter ablation, but not in thoracoscopic maze.